Implementation of Digital Marketing Communication for Secondate Cosmetic Brand - Himawan, Sienny; Sutikno, Devica (Jurnal Komunikasi dan Bisnis, 2024)
Secondate is a local cosmetics brand from Jakarta, Indonesia, established in 2020. The owners of Secondate are a popular beauty influencer, Titan Tyra, and Gitta Amelia, a young entrepreneur and talented investor. Secondate is a beauty brand that not only sells products but also shares stories about women's insecurities and various issues, based on real-life experiences. Secondate places great importance on digital marketing communication at every step, especially on Instagram. Secondate has various digital platforms and offline stores to sell their products. Their campaigns have successfully increased consumer attention, brand awareness, and brand engagement. This research, using qualitative methods with an observational and documentation approach, aims to provide valuable insights for other companies looking to adopt similar strategies in their digital marketing. By understanding how Secondate integrates customer stories, other companies can learn how to enhance customer relationships and strengthen brand engagement through a more personal and authentic approach. The results of this study show that Secondate has successfully used effective digital marketing communication strategies through many platforms. Secondate aims to create a memorable brand through their products and campaigns, emphasizing the importance of marketing communication in the digital era.